2013
DOI: 10.1177/000348941312201202
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Obstruction and Unilateral Chronic Otitis Media: Evaluation by Acoustic Rhinometry

Abstract: These findings do not support the hypothesis that unilateral COM is correlated with the side of nasal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We conducted an objective evaluation of the relationship between nasal functions and middle-ear pathology by measuring nasal functions with active anterior rhinomanometry, which is considered the ideal method for nasal function evaluation. Our results were similar to those of Toros et al 16 . and Güçlü et al ., 15 and our objective measurements of nasal functions revealed no differences between the affected and unaffected sides in unilateral chronic otitis media patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We conducted an objective evaluation of the relationship between nasal functions and middle-ear pathology by measuring nasal functions with active anterior rhinomanometry, which is considered the ideal method for nasal function evaluation. Our results were similar to those of Toros et al 16 . and Güçlü et al ., 15 and our objective measurements of nasal functions revealed no differences between the affected and unaffected sides in unilateral chronic otitis media patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Toros et al . found no differences in the acoustic rhinometry measurements of nasal functions of the affected and unaffected sides in 55 patients with unilateral chronic otitis media 16 …”
Section: Discussionmentioning
confidence: 82%
“…But, using the same technique, Arsla et al 8 did not find significant differences in nasal airway resistance between the COM sides and unaffected sides between 102 patients with unilateral COM and 40 individuals without any ear or nasal pathologies controls. And Toros et al 10 did not observe correlation between the ear with COM and the side of nasal obstruction by acoustic rhinometric in a sample of 55 patient with COM. Studying 114 patients with COM, Ural et al 5 suggested that septal deviation occurred more frequently on the same side of ear pathology in patients with tubotympanic chronic suppurative otitis media, but not in patients with atticoantral chronic suppurative otitis media.…”
Section: Discussionmentioning
confidence: 88%
“…However, the relationship between the nose conditions and COM is controversial. While some authors have found a significant correlation between the incidence of nasal pathology and COM, 4–7 others do not find such a correlation 8–11 . Regardless of the role of alterations of the nose and/or nasopharynx on the middle ear, the intimate knowledge of this relationship would be of great interest for the treatment of patients with COM and concomitant nasal and/or nasopharyngeal alterations, a very common situation in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation